The Impact of SERVQUAL Dimensions on Customer Satisfaction in Education and Training: An Economic Perspective - Suryaman, Maman; Tukiran, Martinus (Yayasan Riset dan Pengembangan Intelektual, 2025)
This study investigates the influence of the five SERVQUAL dimensions—tangible, empathy, reliability, responsiveness, and assurance—on customer satisfaction in education and training institutions using a Systematic Literature Review (SLR) approach. The research aims to synthesize findings from empirical studies published between 2020 and 2024 to provide a comprehensive understanding of how these dimensions impact customer satisfaction in this context. The review systematically collected and analyzed relevant literature from reputable databases, including Dimention. A total of 9 studies were selected based on predefined inclusion and exclusion criteria, ensuring that only research focusing on SERVQUAL dimensions in education and training institutions and their impact on customer satisfaction was included.The results reveal that all five dimensions significantly contribute to customer satisfaction, with reliability and assurance having the strongest impact. Tangible aspects, such as facilities and infrastructure, and empathy, which reflects personalized attention, also play crucial roles. Responsiveness, related to the promptness and willingness of service delivery, was found to enhance trust and loyalty among customers. This study highlights the critical importance of implementing and improving SERVQUAL dimensions to enhance service quality and satisfaction in education and training institutions. The findings provide valuable insights for educators, policymakers, and administrators to refine service delivery models and meet the growing expectations of their customers.